Foreign debt: encourages or inhibits economic growth (empirical study in ASEAN countries) - Syaparuddin Syaparuddin (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
This research aims to analyze : (1) The pattern of foreign debt change and economic growth in Asean (South East Asia) countries, (2) does foreign debt encourage or inhibit economic growth in Asean (South East Asia) countries. Technique of data analysis utilising qualitative descriptive method and quantitative. Pattern of foreign debt change and economic growth in Asean countries (South East Asia) utilising descriptive analysis. In analyzing whether foreign debt encourage or inhibit economic growth in Asean (South East Asia) countries is used Panel Data Regression. The result shows the pattern of foreign debt’s development in Asean (South East Asia) countries is fluctuated and tend to increase in several countries, as like Indonesia, Malaysia, and Vietnam. In the meantime Myanmar tend to be stable. The pattern of economic growth in Asean countries during 1990-2017 is fluctuated and there are no countries possess an even increasing pattern of growth. Moreover, none even unstable. The result proves that foreign debt has been inhibited economic growth in Asean countries during 1990-2017.